PENGARUH FINANCIAL TECHNOLOGY DAN SOCIAL MEDIA TERHADAP VOLUME PENJUALAN (Studi Pada UMKM Pengguna Aplikasi Layanan Pesan Antar di Kecamatan Bina Widya Kota Pekanbaru) - Intani, Fivin; Ruzikna, Ruzikna (Jurnal Daya Saing, 2024)
Abstract: The objective of this study is to eximine the impact of financial technology (X1) and social media (X2) on sales volume (Y) on MSMEs using delivery services in Binawidya district, Pekanbaru city. This study employs a quantitative methodology, utilizing a questionnaire distributed to 60 MSMEs. The data analysis technique employed is multiple linear regression analysis using the statistical software package SPSS version 25. The result of the analysis indicate that, in that, financial technology has a positive effect on sales volume. This is evidenced by the t-count, which is the greater than the t-table value (3,571 > 1,296). The results indicate that social media has a positive effect on sales volume. This is evidenced by a t-count value that exceeds the table (4,737 > 1,296). Furthermore, the F test reveals that there is a simultaneous relationship betweem variable X1, X2 and Y, as evidenced by a F count value that surpasses tha F-table value (11,554 > 3,14).Keywords : Financial Technology, Social Media, Sales Volume, Delivery Services